THE CURCUMIN CONTENT OF TEMULAWAK(Curcuma xanthorriza Roxb.) RHIZOME AS AFFECTED BY N, K AND MICRONUTRIENTS B, Fe, Zn - Nihayati, Ellis; Wardiyati, Tatik; Retnowati, Rurini; Soemarno, Soemarno (AGRIVITA, Journal of Agricultural Science, 2013)
A polybag experiment to study the influence of N, K, and micronutrients B, Fe, Zn and the curcumin content in temulawak was conducted in Malang from February â September 2012. Using RBD, 8 treatments (P1Â  Inseptisol, without fertilizer, P2Â  InseptisolÂ  300 urea kg.ha-1, P3Â  InseptisolÂ  200 KCl kg.ha-1, P4Â  InseptisolÂ  300 kg.ha-1and 200 kg.ha-1 urea and KCl, P5Â  Alfisol, without fertilizer, P6Â  AlfisolÂ  300 urea kg.ha-1, P7Â  AlfisolÂ  200 KCl kg.ha-1, P8Â  AlfisolÂ  300 kg.ha-1 and 200 kg.ha-1 urea and KCl in 3 replications. The micronutrients in vitro applied RCD by 4 treatments (MS medium, MS without B, Fe and Zn) in 10 replications. The results of experiment showed that dry weight of rhizome per plant in Inseptisol and Alfisol is 30.98 and 9.75 g, content of curcumin 6 month after planting was 3.60 and 4.72%. The highest rhizome weight of 8 months after planting was a combination of N and K of Inseptisol (48.28) and Alfisol (35.75 g per plant).The highest content of curcumin 6 months after planting was on Alfisol (7.99%) and Inseptisol (6.7%) by 200 KCl kg.ha-1.The curcumin content in complete media was higher than that without B, Fe and Zn i.e. 6.26 compared with 1.86â2.39%.Â Keywords : temulawak (Curcuma xanthorriza Roxb. Synm. Curcuma javanica), N, K, B, Fe, Zn, curcumin content